KEEFEKTIFAN KALIMAT DALAM PARAGRAF EKSPOSISI PADA KARANGAN PESERTA PLPG UNIVERSITAS PGRI ADI BUANA SURABAYA - Ira, Retnosari Eko (LPPM Universitas PGRI Adi Buana Surabaya, 2015)
Effective sentence is a sentence that can represent and give rise to back the idea of ​​the author as easy, clear, and complete exactly the same in the reader's mind as to what the author intended. This research will describe the effectiveness of sentences within paragraphs exposition. This study appliesa qualitative approach. The data source of this study is expository paragraph participants of teachers sertification program region 142 and the data of this study are the sentences contained in expository paragraph. Collecting data in this research is done through documentation method. The data collection technique was (1) the data collection, (2) copying tasks, (3) readings expository paragraph, (4) marking with highlighter, (5) classification, (6) coding, and (7) making cards. The data analysis used descriptive method. The stages of data analysis process include (1) the data collection, (2) classification of data, (3) the determination of errors frequency, (4) explanation. This result of this journal was expository paragraph written by participants of teachers sertification program ineffective. The ineffectiveness was found in (1) the unclearness of the idea, (2) the carelesness, and (3) the errors inusing spelling. This study is expected to provide motivation to teachers and other interested parties to pay more attention in writing. Writing effective sentences, the ideas submitted will be understood the reader and the writer